Embodied Cognition in Practice: Exploring Effects of a Motor-Based Problem-Solving Intervention. Issue 6 (3rd June 2019) - Harbourne, Regina T; Berger, Sarah E
Abstract: Background: Embodied cognition interests physical therapists because efforts to advance motor skills in young infants can affect learning. However, we do not know if simply advancing motor skill is enough to support advances in cognition. Objective: The objective was to examine the effect of 2 interventions on the developing motor skill of sitting and problem solving and to describe the feasibility of using eye-tracking technology to explore visual and motor interaction. Design: This was a longitudinal, randomized comparison of interventions. Methods: Twenty infants with developmental delay and/or cerebral palsy, ranging in age from 8 to 34 months (mean [SD] = 15 [6.9] months), participated in an intervention emphasizing motor-based problem solving, and an intervention focused on advancing motor skill through assistance for attaining optimal movement patterns. Outcome measures were the Gross Motor Function Measure sitting subsection and the Early Problem Solving for Infants test. Active touch and looks were measured with eye-tracking technology. Results: Participants in both groups made significant motor gains from baseline, with no difference between intervention groups on Gross Motor Function Measure change scores. Participants in the problem-solving group showed significant gains in Early Problem Solving for Infants scores over the participants in the optimal movement patterns group. Overall, participants increased active touch of toys and increased concurrent looking with active touching. Limitations: This exploratory study was small, with variation in participants' skills. The sampled behaviors for analysis were a small portion of the overall function of the participant. Conclusions: An intervention using motor-based problem solving could improve infants' problem-solving skill. The use of eye-tracking could help to understand embodied cognition as infants develop, but the challenges of embedding the method in natural settings require further work. Listen to the author interview at https://academic.oup.com/ptj/pages/podcasts